2007
DOI: 10.1007/s00221-007-1126-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in corrected and inhibited pointing movements

Abstract: It has been widely reported that aging is accompanied by a decline in motor skill performance and in particular, it has been shown that older subjects take longer to adapt their ongoing reach in response to a target location shift. In the present experiment, we investigated the inXuence of aging on the ability to perform trajectory corrections in response to a target jump, but also assessed inhibition by asking a younger and an older group of participants to either adapt or stop their ongoing movement in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Nevertheless, although older adults are less efficient in adjusting online their action while identifying the first target, their pointing accuracy did not differ significantly from young adults. The finding appears to be consistent with previous research (e.g., Rossit & Harvey, 2007;Sarlegna, 2006) showing that although older adults' correction time is longer than that of young adults, their performance accuracy is similar to that of young adults.…”
Section: Aging and The Limits Of Attention For Perception And Actionsupporting
confidence: 91%
“…Nevertheless, although older adults are less efficient in adjusting online their action while identifying the first target, their pointing accuracy did not differ significantly from young adults. The finding appears to be consistent with previous research (e.g., Rossit & Harvey, 2007;Sarlegna, 2006) showing that although older adults' correction time is longer than that of young adults, their performance accuracy is similar to that of young adults.…”
Section: Aging and The Limits Of Attention For Perception And Actionsupporting
confidence: 91%
“…The difference between young and old participants was 2,4-fold higher for MT compared to PMT (Bautmans, Vantieghem et al 2011). This is in line with other RT studies (Gorus, De Raedt et al 2006;Rossit and Harvey 2008;Wolkorte, Kamphuis et al 2014) showing that the age-related increase of RT in healthy and cognitively intact older persons is most pronounced during the movement phase of the RT task. Interestingly, Bautmans et al have shown that in older persons, longer RT was significantly (p=0.001) related to a higher early co-activation of the antagonist muscle during the PMT, i.e.…”
Section: Introductionsupporting
confidence: 90%
“…The incapacity to refrain from movement initiation while observing the moving stimulus would confirm these clinical observations, uncovering a dependence on environmental cues which is known as environmental dependency syndrome, and commonly seen in people with frontal lobes damages (Lhermitte, 1986). Indeed, topographical (Double et al, 1996), imaging (Scahill et al, 2002) and behavioural (Rossit and Harvey, 2008) studies reported morphology and metabolism alterations of the frontal lobes in AD patients that may explain this unrestrained behaviour. However, alterations in frontal areas, similar to what is seen in AD patients, have also been described in normal elderly people (Double et al, 1996;Salat et al, 1999Salat et al, , 2001 suggesting that the behavioural differences between AD and healthy age-matched participants could not be attributed only to frontal lobes damages.…”
Section: Uncontrolled Initiation Of Ad Patients' Motor Response Whilementioning
confidence: 67%